Bullfighting as dark tourism: cultural experience or anachronism? - Fennell, David A.; Sheppard, Valerie A. (Frontiers in Sustainable Tourism, 2024)
New research in the fast-emerging domain of tourism and animal ethics indicates that the instrumental and utilitarian use of animals in tourism is no longer accepted as a favourable norm. Some of this pressure is coming from the tourists themselves who are increasingly questioning the ethics of such uses. We test this premise through research on one of the most contested forms of animal-based tourism in the form of the Spanish bullfight. Our purpose was to gain a qualitative understanding of ethical issues related to bullfighting, as well as to offer insight for understanding factors that affect tourists' overall evaluation of travel experience at this attraction. The study is informed by a framework on animals as dark tourism attractions, with the central aim of investigating the attitudes of tourists towards bullfighting as one of several variables included in the framework. Emphasis was placed on looking for patterns in concepts and how they are communicated; understanding intentions of individuals; identifying propaganda and bias in communication; and understanding consequences of communication, particularly as it relates to a tourism destination's image. Employing a thematic analysis of 74 TripAdvisor posts, dated from May of 2014 through to November 2022, we found that the majority of posts reflected negative perceptions associated with bullfighting, including cruelty, unfair 'fight,' and torture. In contrast, a minority of posts reflected positive perceptions, including culture, ceremony, pomp, and history. These findings have potential implications for the image of tourism destinations, such as Spain, as dark tourism attractions.